2012
DOI: 10.1007/s12298-012-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Zinc – An Indispensable Micronutrient

Abstract: Availability of Zn to plant is hampered by its immobile nature and adverse soil conditions. Thus, Zn deficiency is observed even though high amount is available in soil. Root-shoot barrier, a major controller of zinc transport in plant is highly affected by changes in the anatomical structure of conducting tissue and adverse soil conditions like pH, clay content, calcium carbonate content, etc. Zn deficiency results in severe yield losses and in acute cases plant death. Zn deficiency in edible plant parts resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(138 citation statements)
references
References 91 publications
2
135
0
1
Order By: Relevance
“…Nevertheless, studies have reported that for current varieties, the polished rice grains supply only one fifth of daily Zn requirements (Prom-uthai et al 2010, Sharma et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have reported that for current varieties, the polished rice grains supply only one fifth of daily Zn requirements (Prom-uthai et al 2010, Sharma et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…This process has been used to successfully improve the bioavailability or levels of β-carotene in rice, Zn and Fe in wheat grain as well as levels of other nutrients in other crops [4]. As a result, a number of strategies have been deployed to improve nutritional quality in wheat, such as conventional, technological and transgenic approaches that were undertaken in eforts to improve the levels and bioavailability of micronutrients and phenolic acids, mainly through the biofortiication route [17,21,27,28]. This includes several eforts that managed to successfully increase the total grain nutrient content and bioavailability of some micronutrients through genetic biofortiication, agronomic biofortiication, the use of bioavailability enhancers, including genetic modiication through transforming the plants with the ferritin gene, which may not be desirable by the public.…”
Section: +mentioning
confidence: 99%
“…This includes success in increasing the bioavailability of Fe and Zn and decreasing the antinutrients such as phytic acid and polyphenols, which inhibit Fe absorption thereby reducing Fe bioavailability. However, a series of strategies to improve the bioavailability of micronutrients and phenolic acids have been deployed, this includes agronomic biofortiication and the use of nutritional enhancers [27,28,38]. Micronutrients and phenolic acids have also been reported to be pres-ent at high concentrations in the outer layers of the seed and in the wheat germ region than in the endosperm region [18,34].…”
Section: Progress In Improving Nutritional Qualitymentioning
confidence: 99%
“…Micronutrient-efficient genotypes could provide a number of benefits such as the reduction in the use of fertilizers, improvements in seedling vigor, and resistance to abiotic and biotic stresses (Teklić et al, 2013). Accordingly, in countries where rice is used as staple food, the per capita consumption of this "global grain" (Sharma et al, 2013) is very high, ranging between 62 -190 kg year (Lu et al, 2008). In developing countries, a large percentage of the population has no access to meat in their diet; the daily food intake is mostly cereal-based and does not support the microelement and vitamin needs of the population, as well as the biochemical diversity of food needed for a healthy life (Mayer et al, 2008).…”
Section: About the Reduction Of Selenium Malnutrition Using Biofortifmentioning
confidence: 99%